Management of Supernumerary Teeth in Children - Linda Sari Sembiring; Dominica Dian; Euis Dara (SONDE (Sound of Dentistry), 2024)
Background supernumerary teeth are an anomaly of tooth development in the form of additional teeth from the normal number, located in the upper and lower jaw arches and can cause tooth malposition. Supernumerary teeth can be classified based on chronology, topography, and morphology. Case 12-year-old boy with complaints of irregular teeth. On intraoral examination, there were supernumerary teeth between the tooth region 12 and tooth 13. Periapical radiographs showed supplemental supernumerary teeth. Case Management extraction of supernumerary teeth with topical gel anesthesia technique and infiltration in the mucobuccofold with 0.5 ml of pehacaine and in the palatine as much as 0.5 ml. Supernumerary teeth were loosened from their sockets using an elevator and removed using forceps. Extraction was carried out carefully because the position of the supernumerary teeth was close to the roots of the erupted premolar teeth. Discussion supplemental supernumerary teeth resemble normal teeth and often cause tooth crowding. Supernumerary teeth located between teeth 12 and 13 cause the position of tooth 13 to be labioverted. Conclusion early diagnosis through clinical and radiographic examination is important in determining the right treatment plan. Extraction of supernumerary teeth in this case was carried out carefully to prevent damage to the roots of permanent teeth located near the supernumerary teeth Keywords: Supernumerary; extraction; infiltration; crowding